Coefficient Results on Certain Subclasses of Sakaguchi Type Bi-univalent Functions (European Journal of Pure and Applied Mathematics, 2025)
In this article, we study some subclasses of Sakaguchi type bi-univalent functions associated with Gegenbauer polynomials and Einstein function. We explore certain properties of functions belonging to these subclasses, including coefficient bounds and the Fekete–Szeg\"o functionals. This research generalise and improves the related works of several earlier authors.
Keywords: analytic functions; bi-univalent functions; convolution; Gegenbauer polynomial; Einstein function; Sakaguchi type function; coefficient estimate; Fekete-Szeg\"o